High frequency of methicillin-susceptible and methicillin-resistant Staphylococcus aureus in children under 1 year old with skin and soft tissue infections - Salazar-Ospina,Lorena (2018)
Abstract Objective: Staphylococcus aureus is responsible for a large number of infections in pediatric population; however, information about the behavior of such infections in this population is limited. The aim of the study was to describe the clinical, epidemiological, and molecular characteristics of infections caused by methicillin-susceptible and resistant S. aureus (MSSA-MRSA) in a pediatric population. Method: A cross-sectional descriptive study in patients from birth to 14 years of age from three high-complexity institutions was conducted (2008-2010). All patients infected with methicillin-resistant S. aureus and a representative sample of patients infected with methicillin-susceptible S. aureus were included. Clinical and epidemiological information was obtained from medical records and molecular characterization included spa typing, pulsed-field gel electrophoresis (PFGE), and multilocus sequence typing (MLST). In addition, staphylococcal cassette chromosome mec (SCCmec) and virulence factor genes were detected. Results: A total of 182 patients, 65 with methicillin-susceptible S. aureus infections and 117 with methicillin-resistant S. aureus infections, were included in the study; 41.4% of the patients being under 1 year. The most frequent infections were of the skin and soft tissues. Backgrounds such as having stayed in day care centers and previous use of antibiotics were more common in patients with methicillin-resistant S. aureus infections (p ≤ 0.05). Sixteen clonal complexes were identified and methicillin-susceptible S. aureus strains were more diverse. The most common cassette was staphylococcal cassette chromosomemec IVc (70.8%), which was linked to Panton-Valentine leukocidin (pvl). Conclusions: In contrast with other locations, a prevalence of infections in children under 1 year of age in the city could be observed; this emphasizes the importance of epidemiological knowledge at the local level.